Design of Solar Optical Fiber Lighting System for Enhanced Lighting in Highway Tunnel Threshold Zone: A Case Study of Huashuyan Tunnel in China - Xiaochun Qin; Xuefeng Zhang; Shuai Qi; Hao Han (International Journal of Photoenergy)
In this paper, the principle, structural composition, materials, and characteristics of solar optical fiber lighting system were discussed. The different luminance requirements of different zones of highway tunnel were identified on the basis of the analysis of tunnel lighting considering drivers’ visually self-accommodating physiological function for luminance change. Taken Huashuyan Tunnel of G109 Highway located in Hohhot of Inner Mongolia in China as the case study, the system design of solar optical fiber lighting for enhanced lighting in threshold zone of highway tunnel was made. It was indicated through calculation that the design length of solar optical fiber enhanced lighting was related to the design speed, longitudinal slope, and overhead clearance of the tunnel, and the design luminance of solar optical fiber enhanced lighting was related to the luminance outside the tunnel, the design speed, and the design traffic flow of the tunnel. Luminance analysis of the solar optical fiber lighting system of Huashuyan Tunnel was made based on the on-site experiment. Also, the 3D illuminance simulation results by DIALux software were made to indicate that the solar optical fiber lighting system in Huashuyan Tunnel still well met the enhanced lighting demand even not considering the contribution of LED lighting.